Mass media influences on body image and body esteem in female adolescents: the mediating role of hopeful future expectations. Issue 4 (8th August 2021) - Musetti, Alessandro; Schimmenti, Adriano; Corsano, Paola
ABSTRACT: Mass media influences to achieve ideal body image are widely posited to be an antecedent of low body esteem in females. In this study, we aimed to examine the relationship between mass media influence on body image and body esteem, with a focus on the mediating role of hopeful future expectations in a sample of female adolescents. Body esteem, mass media influences on body image, and hopeful future expectations were evaluated in 280 Italian female adolescents by means of questionnaires. Mass media influences on body image are negatively associated with body esteem, and hopeful expectations for the future are positively associated with body esteem. The negative influence of mass media pressures on body esteem was partially mediated by hopeful expectations for the future. Clinicians dealing with adolescents with low body esteem may consider how female adolescents internalize sociocultural body ideals and how this internalization might affect their future expectations and body esteem.